2022
DOI: 10.1021/acsbiomedchemau.2c00003
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin: A Promising Nanoreactor and Nanocarrier for Bionanotechnology

Abstract: The essence of bionanotechnology lies in the application of nanotechnology/nanomaterials to solve the biological problems. Quantum dots and nanoparticles hold potential biomedical applications, but their inherent problems such as low solubility and associated toxicity due to their interactions at nonspecific target sites is a major concern. The self-assembled, thermostable, ferritin protein nanocages possessing natural iron scavenging ability have emerged as a potential solution to all the above-mentioned prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 311 publications
0
28
0
1
Order By: Relevance
“…For instance, smaller nanoparticles (< 20 nm) are more easily transported to the lymph nodes [ 148 ] and are most capable of perturbing membranes [ 149 , 150 ], whereas intermediate-sized nanoparticles (20–100nm) are most capable of circulating in the blood for long periods of time and avoiding clearance [ 148 ]. Superparamagnetic iron oxide, platinum, gold, silver, quantum dots (composed of group IIB-VIA or group IIIA-VA elements on the periodic table), and other inorganic nanoparticles have been demonstrated to be useful to a wide range of biomedical applications including targeted delivery of drugs, biosensing, imaging, antimicrobial therapy, and photothermal therapy [ 105 , [150] , [151] , [152] , [153] , [154] , [155] ]. Drawbacks to their clinical use, however, includes their toxicity, induced by harmful metal ions or uncontrolled protein corona formation, poor solubility, and propensity to aggregate into structures larger than their optimal nano-size [ 152 , 154 , 156 , 157 ].…”
Section: Biomedical Applications Of Ferritinmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, smaller nanoparticles (< 20 nm) are more easily transported to the lymph nodes [ 148 ] and are most capable of perturbing membranes [ 149 , 150 ], whereas intermediate-sized nanoparticles (20–100nm) are most capable of circulating in the blood for long periods of time and avoiding clearance [ 148 ]. Superparamagnetic iron oxide, platinum, gold, silver, quantum dots (composed of group IIB-VIA or group IIIA-VA elements on the periodic table), and other inorganic nanoparticles have been demonstrated to be useful to a wide range of biomedical applications including targeted delivery of drugs, biosensing, imaging, antimicrobial therapy, and photothermal therapy [ 105 , [150] , [151] , [152] , [153] , [154] , [155] ]. Drawbacks to their clinical use, however, includes their toxicity, induced by harmful metal ions or uncontrolled protein corona formation, poor solubility, and propensity to aggregate into structures larger than their optimal nano-size [ 152 , 154 , 156 , 157 ].…”
Section: Biomedical Applications Of Ferritinmentioning
confidence: 99%
“…These highly desirable characteristics have allowed for the application of ferritin as an “inorganic material” in medicine [ [152] , [153] , [154] ]. For instance, apoferritin has been successfully used as a biotemplate for synthesizing CdSe, CdS, ZnSe, ZnS, PbS, and other quantum dots within its protein shell, mimicking ferritin's natural iron biomineralization process, and allowing for enhanced biocompatibility of these materials [ 151 ].…”
Section: Biomedical Applications Of Ferritinmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to the capacities that ferritin offers, ferritin nanocages have been proposed in many studies as vaccine platforms against different diseases, including cancer [ 21 , 22 , 23 ], various viruses [ 24 , 25 , 26 ], and other pathogens [ 27 ]. It has been shown that ferritin nanocages have lymph-node target ability, which makes them able to elicit efficient antigen delivery to antigen-presenting cells (APCs) [ 22 , 28 ], high immunogenicity [ 27 , 29 ], and stability [ 30 , 31 ]. Moreover, the structure of ferritin has the advantage of displaying various antigens by fusing to their surface [ 27 , 32 ].…”
Section: Introductionmentioning
confidence: 99%